Quality of Kani-Ban water as a main tributary of Tanjero River for irrigation purposes - Hamasalh, Nizar Yaseen; Ahmaad, Ali Bawasheakh (Sulaimani Journal for Pure and Applied Sciences, 2015)
The current study was undertaken to evaluate the suitability of Kani-Ban stream water as one of the main tributary of Tanjero River in Sulaimani for irrigation purpose. Water samples were collected from (6) various locations from November (2013) to April (2014). Water samples were analyzed the various physico-chemical parameters, such as, pH, Electrical Conductivity (EC), Total dissolved solids (TDS), Na+, K+, Ca2+, Mg2+, HCO3 -, CO3 2-, SO4 2-, Cl-, B, and NO3-. The present work is a trial to evaluate and classify the water quality of Kani-Ban stream for irrigation purpose, by using the model of Irrigation water quality index (IWQI) developed in Brazil .The results obtained on (IWQI) for all sampling sites were within the class of use with no restrictions (excellent) for irrigation. According to the EC and SAR plotted on the US salinity diagram, it is illustrated that water samples of Kani- Ban stream fall in the class of (C2-S1) for locations (1, 2, 3, and 4) indicating medium salinity with low sodium hazards, while other locations (5 and 6) fall in the class of (C3-S1) indicating high salinity with low sodium hazards which can be used for irrigation. While as sodium adsorption ratio (SAR) , all the water samples fell under ‘Low’ class and as per salinity classification (US salinity diagram); all the irrigation water samples fell under low sodium hazards (S1) 1class it means these water samples are suitable for irrigation. The residual sodium carbonate (RSC) values of all water samples under “Safe” category.
Keywords: Irrigation Water quality; index IWQI; Water classification; Salinity hazard; Sodicity hazard